2018
DOI: 10.1007/s12094-018-1930-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of circulating tumor cells in squamous cell carcinoma of the head and neck and patient outcomes

Abstract: Liquid biopsy techniques in HNSCC show promise as a means of identifying patients at greater risk of disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The results of the present study are in accordance with other studies investigating CTCs in solid cancers, including the head and neck, which revealed that the presence of CTCs may influence prognosis (11)(12)(13)(14)(15)(16)(17)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) similar to what was observed in the patients in the present study (6/8 were positive to CTC preoperatively). A recent meta-analysis comprised of 17 studies confirmed the significant prognostic value of CTCs in patients with head and neck cancer, wherein positive CTCs were significantly associated with poor overall, disease-free and progression-free survival (61).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study are in accordance with other studies investigating CTCs in solid cancers, including the head and neck, which revealed that the presence of CTCs may influence prognosis (11)(12)(13)(14)(15)(16)(17)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57) similar to what was observed in the patients in the present study (6/8 were positive to CTC preoperatively). A recent meta-analysis comprised of 17 studies confirmed the significant prognostic value of CTCs in patients with head and neck cancer, wherein positive CTCs were significantly associated with poor overall, disease-free and progression-free survival (61).…”
Section: Discussionsupporting
confidence: 92%
“…Prevention and early detection of distant metastasis are currently the best options available for OSCC. In the near future, analysis of genetic mutations using liquid biopsy samples may allow us to diagnose distant metastasis early during the initial treatment and ensure timely treatment 17 . In other words, conducting regular systematic checkups in patients with OSCC for risk factors for distant metastasis and implementing appropriate drug therapy should be mandatory.…”
Section: Discussionmentioning
confidence: 99%
“…In the latest study, Morgan et al used surface-enhanced Raman scattering (SERS) nanotechnology identified amounts of CTCs in HNSCC. 32 They demonstrated that the number of CTCs was correlated with the disease progression of HNSCC patients, and the level of CTCs was a strong indicator of poor prognosis. In this study, we found that PFS and OS of HNSCC patients with CTCs-positive were shorter than those of CTCs-negative patients by survival analysis, which is consistent with most of the previous studies.…”
Section: Discussionmentioning
confidence: 99%